Terahertz studies of carrier localization in spontaneously forming polar lateral heterostructures. Issue 11 (26th August 2013) - Metcalfe, Grace D.; Hirai, Asako; Young, Erin C.; Speck, James S.; Shen, Hongen; Wraback, Michael
Abstract We employ near‐bandgap terahertz emission spectroscopy to study lateral heterostructures resulting from basal plane stacking faults in m ‐plane GaN. The predominant stacking faults have I1 character and behave as an array of spontaneously forming layers comprised of a single cubic stacking sequence within the wurtzite matrix that terminate the spontaneous polarization along the in‐plane c‐axis, leading to strong lateral electric fields. Spectral tuning of femtosecond excitation pulses enables observation of the transition from carrier transport in the continuum to formation of instantaneous dipoles and nonlinear susceptibility associated with both the quantum‐well‐like regions of the cubic layers and polarization‐induced triangular‐like potentials. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)